TRANSITIVITAS PADA TEKS CERPEN HARIAN KOMPAS (KAJIAN LINGUISTIK FUNGSIONAL SISTEMIK) - Nurrahmah Nurrahmah; Wirduna Wirduna; Yusri Yusri; Subhayni Subhayni (Jurnal Dedikasi Pendidikan, 2020)
This research is aimed to describe the transitivity of the short story text in daily Kompas. this study emphasize the usage of the processes, participants, and circumstances types that exists in the clause structure of the short story text. The approachment  used in this research was qualitative approachment through content analysis based on systemic functional linguistic. The data source in this research were the 2013 period of the short story text in daily Kompas and as the data, five short story text  would be analyzed. The result of this research were shown that the short story text in daily Kompas dominated by material processes total 317. Then, participants type of short story text dominated by an actor total 155.  Afterwards, circumstances type, the short story text dominated by location type included places and times total 93. It shown that the short story text in daily Kompas tells about an event within involved an action and used many background, places, and times.